Water quality in the Santa Cruz of the Apodi watershed, Rio Grande do Norte, Brazil - Silva, Wagner Bandeira da; Bezerra, Joel Medeiros; Rêgo, Alana Ticiane Alves do (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
The adverse impacts in the Santa Cruz do Apodi Watershed Basin (BHASCA) prevent multiple uses of water in certain areas, making it necessary to understand the quality of this resource through a specific assessment of its physical, chemical and biological characteristics. In this context, the present study aimed to characterize the main components that influence the water quality of the watershed of the Santa Cruz do Apodi-RN reservoir, from 2008 to 2016, considering the seasonal variability. The methodology consisted of conducting, by means of a survey of secondary data, derived from the reports of the Água Azul Program, an analysis of the water quality parameters at BHASCA, through the application of statistical techniques of Pearson's linear correlation matrix and Principal Components Analysis (ACP). The linear correlation made it possible to identify the dependence between physical-chemical and biological parameters. ACP synthesized the information contained in the set of variables. In this perspective, BHASCA's susceptibility to eutrophication processes was observed, which may be compromising and/or limiting the multiple uses of water in the referred basin, affecting the maintenance of biodiversity.